Pelanggaran Prinsip Kesantunan Pada Film Pendek Komedi di Channel Youtube Lula Studio - Inna Maya Sari; Djoko Sulaksono; Kenfitria Wijayanti (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2023)
Politeness principles violations still present in movies, including short comedy movies in Lula Studio Youtube channel. It becomes a concern as such violations may serve as a model for people who watch the movies. Therefore, the present study attempted to depict the forms of politeness principle violation in short comedy movies in Lula Studio and provided a reference to minimize further language impoliteness. To this end, a descriptive qualitative with pragmatic approach was applied. The data in this study were speech among the movie actors, collected through document analysis and researchers’ note. The movie samples were selected using the purposive sampling technique. Theory triangulation was applied to ensure the data validity. The data were analyzed using flow analysis technique. Twenty one violations were noticed from seven movies in Lula studio, which covers Leech’s six language politeness maxims and Asim Gunawan’s four language politeness maxims.